Epidemiology, risk factors, and molecular characterization of occult hepatitis B infection among anti‐hepatitis B core antigen alone subjects. Issue 4 (8th November 2018) - Azarkar, Zohreh; Ziaee, Masood; Ebrahimzadeh, Azadeh; Sharifzadeh, Gholamreza; Javanmard, Davod
Abstract : Objectives: Features of occult hepatitis B virus (HBV) infection among the anti‐hepatitis B core antigen (anti‐HBc) positives have yet to be described in more details. This study aimed to determine the molecular prevalence of occult HBV infection (OBI), and association to risk factors among seropositives for anti‐HBc. Methods: This was part of a community‐based screening project that included 5234 cases. All participants completed a questionnaire on demographic and socio‐epidemiological information. Then, the blood samples were collected and tested for anti‐HBc and HBsAg using ELISA method. To identify OBI, nested‐polymerase chain reaction (PCR) assays were performed for HBV‐S and X genes, and viral load was determined using an in‐house real‐time PCR. Sequencing and phylogenetic analysis have been implemented for genotyping. Results: Overall, 596 cases, positive only for anti‐HBc were included in the study. OBI was detected among 61 cases (10.2%). The genotype and subgenotype of HBV among all of them was D1, except one that was D4. Most of them had low viral loads ranged from 1.2 × 10 2 to 1.34 × 10 3  copies/mL; 19.6% had undetectable viral loads. Important mutations in surface protein and reverse transcriptase were sI92T, sQ129H, rtL80I, rtS85F, rtL91I. The prevalence of OBI was related to some risk factors, such as tattooing ( P  = 0.02), sexual activities ( P  = 0.009), and diabetes ( P  = 0.031). Conclusion: Our study suggests that OBI should be considered among anti‐HBc seropositive subjects. This form of HBV infection was accompanied with some mutations, risk factors, and diseases. However, further investigations are needed to determine virological importance of documented mutations.